2017
DOI: 10.3389/fimmu.2017.01415
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease-Derived Circulating Cells Release IL-18 and IL-33 under Ultrafine Particulate Matter Exposure in a Caspase-1/8-Independent Manner

Abstract: Chronic obstructive pulmonary disease (COPD) is considered the fourth-leading causes of death worldwide; COPD is caused by inhalation of noxious indoor and outdoor particles, especially cigarette smoke that represents the first risk factor for this respiratory disorder. To mimic the effects of particulate matter on COPD, we isolated peripheral blood mononuclear cells (PBMCs) and treated them with combustion-generated ultrafine particles (UFPs) obtained from two different fuel mixtures, namely, pure ethylene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 28 publications
3
39
1
Order By: Relevance
“…It has to be noted though, that as already published, the environmental pollution together smoking is another risk factor for lung cancer. Indeed, we found that smokers- and COPD-derived PBMCs treated with air pollutants [ 24 , 25 ], such as particulate matter (PM) of ultrafine sizes, were able to release caspase-4, index of higher risk for lung cancer establishment. A great limitation to this study is the absence of follow-up information about COPD and healthy smokers, in order to better understand and associate the levels of the circulating caspase-4 to the establishment of a tumor mass, avoiding late diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted though, that as already published, the environmental pollution together smoking is another risk factor for lung cancer. Indeed, we found that smokers- and COPD-derived PBMCs treated with air pollutants [ 24 , 25 ], such as particulate matter (PM) of ultrafine sizes, were able to release caspase-4, index of higher risk for lung cancer establishment. A great limitation to this study is the absence of follow-up information about COPD and healthy smokers, in order to better understand and associate the levels of the circulating caspase-4 to the establishment of a tumor mass, avoiding late diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous data (6, 7), we found that the release of IL-1-like cytokines from Soot-treated human cells was correlated to the inflammasome complex. Therefore, because caspase-1 is involved in the inflammasome activation and in IL-1-like cytokine release (12, 13), we treated mice with a well-known caspase-1 inhibitor, Ac-Y-Vad, Y-Vad.…”
Section: Resultsmentioning
confidence: 76%
“…Based on our previous published data, the administration of PMx can alter immune cell phenotype (6, 7). Therefore, we evaluated immune cell infiltration in the lung of the five groups of mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, another important characteristic of PEL+LAT combination is the antioxidant activity, which could be of potential relevance in oxidative stress-based pathologies, such as chronic obstructive pulmonary disease (COPD) [ 12 , 17 , 18 ]. In particular, we observed that PEL+LAT exerted a potentiated antioxidant activity on LPS-treated macrophages.…”
Section: Discussionmentioning
confidence: 99%